Cyberpower : the culture and politics of cyberspace and the Internet - Jordan, Tim, 1959- (Routledge, 1999)
This is the first complete introduction to and analysis of the politics of the internet. Key concepts included are: power and cyberspace; the virtual individual; society in cyberspace, and imagination and the internet.